Hyperammonaemia disrupts daily rhythms reversibly by elevating glutamate in the central circadian pacemaker. (21st November 2022) - Granados‐Fuentes, Daniel; Cho, Kevin; Patti, Gary J.; Costa, Rodolfo; Herzog, Erik D.; Montagnese, Sara
Abstract: Patients with cirrhosis exhibit features of circadian disruption. Hyperammonaemia has been suggested to impair both homeostatic and circadian sleep regulation. Here, we tested if hyperammonaemia directly disrupts circadian rhythm generation in the central pacemaker, the suprachiasmatic nuclei (SCN) of the hypothalamus. Wheel‐running activity was recorded from mice fed with a hyperammonaemic or normal diet for 35 days in a 12:12 light–dark (LD) cycle followed by 15 days in constant darkness (DD). The expression of the clock protein PERIOD2 (PER2) was recorded from SCN explants before, during and after ammonia exposure, ±glutamate receptor antagonists. In LD, hyperammonaemic mice advanced their daily activity onset time by 1 h (16.8 ± 0.3 vs. 18.1 ± 0.04 h, p = .009) and decreased their total activity, concentrating it during the first half of the night. In DD, hyperammonaemia reduced the amplitude of daily activity (551.5 ± 27.7 vs. 724.9 ± 59 counts, p = .007), with no changes in circadian period. Ammonia (≥0.01 mM) rapidly and significantly reduced PER2 amplitude, and slightly increased circadian period. The decrease in PER2 amplitude correlated with decreased synchrony among circadian cells in the SCN and increased extracellular glutamate, which was rescued by AMPA glutamate receptor antagonists. These data suggest that hyperammonaemia affects circadian regulation of rest‐activity behaviour by increasing extracellular glutamate in the SCN.